2019
DOI: 10.3390/polym11111789
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Antimicrobial Polymers with Nanomaterials and Bioactives to Improve Biocidal Therapies

Abstract: The rise of antibiotic-resistant microorganisms has become a critical issue in recent years and has promoted substantial research efforts directed to the development of more effective antimicrobial therapies utilizing different bactericidal mechanisms to neutralize infectious diseases. Modern approaches employ at least two mixed bioactive agents to enhance bactericidal effects. However, the combinations of drugs may not always show a synergistic effect, and further, could also produce adverse effects or stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 172 publications
(172 reference statements)
0
30
0
Order By: Relevance
“…The obtained results revealed that lower E a 's are required to perform these quaternization reaction for halides with shorter alkyl chain lengths (i.e., E a = 54.544 kJ mol −1 for BuI, 64.997 kJ mol −1 for HeI, and 65.390 kJ mol −1 for DeI). The herein described experimental method and the obtained kinetic parameters can be used as a reference for optimizing the conditions of quaternization reactions of polymers with amino pedant groups to access cationic polymeric materials, which, either pristine or in combination with other (nano‐)compounds (e.g., nanoparticles), can be useful as novel antimicrobial or fungicidal systems [ 8,12 ] or in other biological applications (e.g., DNA/RNA delivery systems). [ 22 ] Future contributions in this direction will include the kinetic analysis and comparison of similar quaternization reactions utilizing other series of alkyl halides (e.g., alkyl bromides).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results revealed that lower E a 's are required to perform these quaternization reaction for halides with shorter alkyl chain lengths (i.e., E a = 54.544 kJ mol −1 for BuI, 64.997 kJ mol −1 for HeI, and 65.390 kJ mol −1 for DeI). The herein described experimental method and the obtained kinetic parameters can be used as a reference for optimizing the conditions of quaternization reactions of polymers with amino pedant groups to access cationic polymeric materials, which, either pristine or in combination with other (nano‐)compounds (e.g., nanoparticles), can be useful as novel antimicrobial or fungicidal systems [ 8,12 ] or in other biological applications (e.g., DNA/RNA delivery systems). [ 22 ] Future contributions in this direction will include the kinetic analysis and comparison of similar quaternization reactions utilizing other series of alkyl halides (e.g., alkyl bromides).…”
Section: Discussionmentioning
confidence: 99%
“…Poly[2‐(dimethylamino)ethyl methacrylate] (PDMAEMA) has a tertiary amine structure as pendant group, which in an acidic medium or as a quaternary ammonium salt acquires a cationic character. [ 7 ] Quaternized PDMAEMA is a versatile polymer that can be applied in antimicrobial systems, [ 8 ] such as films with porous surfaces of narrow size, [ 9 ] cationic coatings for silica nanoparticles, [ 10 ] recognition elements against bacteria, [ 11 ] tandem systems based on polymer‐nanoparticles Ca(OH) 2 ‐Mg(OH) 2 with fungicide properties, [ 12 ] or functionalized cellulose surfaces for preparation of fibers or nanocrystals. [ 13,14 ] Among different synthetic techniques, RAFT polymerization has been utilized for the synthesis of PDMAEMA, where reaction parameters such as the chemical nature of the chain transfer agent (CTA), concentration of reagents, and reaction medium have significant effects on the control of molar mass, Ð , and chemical structure of derived polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These halogens can be slowly released into the environment and lead to generating ROS ( Figure 3 d) that can kill faster a broad spectrum of bacteria. In general, the biocidal activity of N-halamines can be restored using halogen-donor compounds (sodium hypochlorite/hypobromite) [ 97 ]. The mechanism of action of N-halamines has been described in two different ways: either the halogen is directly transferred to the microbial cell wall, followed by oxidation, or the dissociation into water is followed by diffusion over the bacteria.…”
Section: Main Antimicrobial Mechanisms Associated With Polymeric Structuresmentioning
confidence: 99%
“…For instance, antimicrobial polymers, such as PEG [ 114 ], PEI [ 188 ], zwitterionic PCBMA [ 189 ] or cationic poly(2-(tert-butylaminoethyl) methacrylate) (PTBAM) [ 190 ] can be utilized along with biocidal metallic NPs (Ag [ 74 ], copper/Cu [ 191 ], etc.) or carbon-based nanostructures [ 97 ] to develop highly biocidal nanocomposites ( Table 6 ). Metallic NPs are increasingly used as an alternative to antibiotics for a myriad of purposes, including antibacterial coatings for implantable devices, to prevent infections [ 41 ].…”
Section: Antimicrobial Surfaces Generated From Polymer-based Nanocompositesmentioning
confidence: 99%